Association between maternal pre-delivery body mass index and offspring overweight/obesity at 1 and 2 years of age among residents of a suburb in Taiwan - Liu,Hsien-Kuan; Wu,Chien-Yi; Yang,Yung-Ning; Wu,Pei-Ling; He,Zong-Rong; Yang,San-Nan; Tey,Shu-Leei (PeerJ, 2019)
Background Overweight and obesity among children can cause metabolic syndrome in adulthood and are a significant public health issue. Some studies suggest that maternal pre-pregnancy body mass index (BMI) and excessive gestational weight gain during pregnancy are associated with overweight and obesity in offspring. However, it is difficult to collect information on accurate pre-pregnancy BMI and pregnancy weight gain for women living in areas where medical resources are scarce. Maternal pre-delivery BMI might be predictive of the risk of overweight and obesity among offspring of pregnant mothers living in suburban areas. Methods We retrospectively collected data on term neonates with appropriate weights for their gestational age born between April 2013 and October 2015. We excluded neonates with major congenital anomalies or diseases and incomplete data. Mothers with systemic diseases or drug abuse were also excluded. Offspring body weights and heights at 1- and 2-years-old were recorded. Maternal pre-delivery BMI was divided into following groups: <25, 25–29.9, and ≧30 kg/m2. Results We included 261 mother-child pairs in this study. The BMIs of the offspring differed significantly among the three maternal pre-delivery BMI groups at the age of 2 years (15.18 ± 1.04, 15.83 ± 1.28, and 16.29 ± 1.61 kg/m2, p < 0.001, respectively). After adjusting for potential cofounders possibly affecting weight using multivariate linear regression, the children’s BMIs (adjusted 95% CI: 0.71 [0.31–1.11]; p = 0.001) and BMI percentiles (adjusted 95% CI 15.80 [7.32–24.28]; p < 0.001) at the age of 2 years were significantly higher in those born to mothers with pre-delivery BMIs of 25–29.9 kg/m2 compared to mothers with pre-delivery BMIs <25 kg/m2. Maternal pre-delivery BMI ≧30 kg/m2 was significantly associated with increased BMIs (adjusted 95% CI: 1.17 [0.72–1.63]; p < 0.001) and BMI percentiles (adjusted 95% CI: 23.48 [13.87–33.09]; p < 0.001) in their children. A maternal pre-delivery BMI of 27.16 kg/m2 was the optimal cut-off for predicting offspring overweight/obesity at the age of 2 years. Discussion Our results indicate that the maternal pre-delivery BMI was significantly associated with offspring BMI and weight gain at the age of 2 years. A maternal pre-delivery BMI of 27.16 kg/m2 might be a useful predictor for estimating the risk of overweight or obesity in offspring at the age of 2 years.
Keywords: Obesity; Maternal pre-delivery BMI; Overweight; Offspring; Body weight